Lack of APLP1 leads to subtle alterations in neuronal morphology but does not affect learning and memory - Erdinger, Susanne; Amrein, Irmgard; Back, Michaela; Ludewig, Susann; Korte, Martin; Engelhardt, Jakob von; Wolfer, David P.; Müller, Ulrike C. (Frontiers in molecular neuroscience, 2022)
The amyloid precursor protein APP plays a crucial role in Alzheimer pathogenesis. Its physiological functions, however, are only beginning to be unraveled. APP belongs to a small gene family, including besides APP the closely related amyloid precursor-like proteins APLP1 and APLP2, that all constitute synaptic adhesion proteins. While APP and APLP2 are ubiquitously expressed, APLP1 is specific for the nervous system. Previous genetic studies, including combined knockouts of several family members, pointed towards a unique role for APLP1, as only APP/APLP1 double knockouts were viable. We now examined brain and neuronal morphology in APLP1 single knockout (KO) animals, that have to date not been studied in detail. Here, we report that APLP1-KO mice show normal spine density in hippocampal CA1 pyramidal cells and subtle alterations in dendritic complexity. Extracellular field recordings revealed normal basal synaptic transmission and no alterations in synaptic plasticity (LTP). Further, behavioral studies revealed in APLP1-KO mice a small deficit in motor function and reduced diurnal locomotor activity, while learning and memory were not affected by the loss of APLP1. In summary, our study indicates that APP family members serve both distinct and overlapping functions that need to be considered for therapeutic treatments of Alzheimer’s disease.